A Multi-Year Assessment of Phytoplankton Fluorescence in a Large Temperate River Reveals the Importance of Scale-Dependent Temporal Patterns Associated With Temperature and Other Physicochemical Variables - Mimouni, El-Amine; Ridal, Jeffrey J.; Twiss, Michael R. (Frontiers in Water, 2021)
An integrated temporal study of a long-term ecological research and monitoring database of the St. Lawrence River was carried out. A long and mostly uninterrupted high temporal resolution record of fluorometric data from 2014 to 2018 was used to examine phytoplankton fluorometric variables at several scales and to identify temporal patterns and their main environmental drivers. Sets of temporal eigenvectors were used as modulating variables in a multiscale codependence analysis to relate the fluorometric variables and various environmental variables at different temporal scales. Fluorometric patterns of phytoplankton biomass in the St. Lawrence River are characterized by large, yearly-scale patterns driven by seasonal changes in water temperature, and to a lesser extent water discharge, over which finer-scale temporal patterns related to colored dissolved organic matter and weather variables can be discerned at shorter time scales. The results suggest that such an approach to characterize phytoplankton biomass in large rivers may be useful for processing large data sets from remote sensing efforts for detecting subtle large-scale changes in water quality due to land use practices and climate change.